Improving Statistics Learning Outcomes through a Differentiated Learning Approach for Students with Various Levels of Ability - Sulistyawati, Wiwik; Fauziyah, Nur; Niswati, Niswati (Proceeding International Conference on Lesson Study, 2023)
Learning is a process of organizing, structuring the environment around students so that they can develop and encourage them to complete the learning process. The learning needs of students must always be the teacher's attention so that each learning process is carried out comfortably, happily and pleasantly, to be able to achieve and effectively implement the learning objectives to be achieved. Differentiated learning is an effort to adapt the learning process in the classroom to meet students' learning needs. Statistics allows students to understand and apply concepts relevant to data analysis, decision making, and problem solving in everyday life. A differentiation approach means providing assignments or activities with different levels of difficulty, providing additional reading materials or resources, and providing guidance or enrichment according to students' needs. Researchers found that the application of differentiated learning can help students to carry out learning activities more optimally. The aim of this research is to explain and evaluate the application of the learning differentiation approach in improving statistics learning outcomes for class VII students with various levels of ability. This research uses descriptive quantitative methods. The data collection methods for this research are observation, formative assessment and documentation. Data analysis uses simple statistical processing using the Sugiyono model. The results of this research show that there was an increase in the average achievement of students' learning objectives from pre-cycle by 71% to 80.65% in cycle I. In cycle II there was an increase in the average achievement of learning objectives by 88.71%. The differentiation learning approach can improve learning outcomes in statistics material in class VIIB UPT SMPN 14 Gresik with various levels of student ability.